(1038) A Critique of Capitalist Strategy for Agricultural Development دراسة نقدية للاستراتيجية الرأسمالية للتنمية الزراعية - I. H. El-Issawy. (INP., 2020)
The performance of agriculture in the last two decades has been very poor in the most under developed countries